Development of Accounting E-Module to Improve Students' Critical Thinking Ability - Ahmad Fadhil Imran; Denies Priantinah; Ismi Solikhatun (Universitas Negeri Makassar, 2022)
This study aims to develop an electronic accounting module with a feasible and effective problem-solving approach to improve students' critical thinking skills in distance learning. This Research and Development (RnD) use the Borg & Gall development model. The feasibility test was carried out by the material, media and teachers as well as students with a pretest and posttest to determine its effectiveness. Data were analyzed using the N-Gain test, Prerequisite Test in the form of normality and homogeneity, including Independent t-test to test the hypothesis. This research produces an accounting e-module product that can be accessed using a flipped book application. This product is declared feasible and effective to improve students' critical thinking skills at SMK Negeri 1 Makassar. The results of the effectiveness test by calculating the N-Gain showed the average value of the experimental class was 56.80, while the average value of the control class was 28.77. The results of the independent t-test analysis also yielded sig values. (2-tailed) <0.05, so the conclusion is that there is a difference in students' critical thinking skills between the experimental class that uses the product and the control class that does not use the product.